Generation, establishment and characterization of three pluripotent stem cell lines (CVTTHi002-A, CVTTHi003-A and CVTTHi004-A) from primary testicular somatic cells isolated from two prepuberal and one peripuberal Klinefelter Syndrome (47 XXY) patients - Myriam Martin-Inaraja; Irene Romayor; Andrea Sáez de Cámara; Lara Herrera; Ainhoa Palacios; Maria Villaverde; Silvia Santos; Miguel Ángel Vesga; Beatriz Barreña; Ana María Aransay; Juan Anguita; Estíbaliz Solorzano; et al. (Stem Cell Research)
Klinefelter Syndrome (KS) is an aneuploid genetic condition in males characterized by at least one additional copy of the X chromosome. Due to fibrotic degeneration of the testis, these patients suffer infertility in the future. The pathogenic mechanism by which this occurs is still not well known. Here, we establish three Induced Pluripotent Stem cell (iPSC) lines derived from prepuberal and peripuberal KS patient’s testicular somatic cells. These could be the first steps towards the creation of an in vitro platform to analyze the molecular mechanisms underlying pathophysiology of the testes in KS patients.